2018
DOI: 10.1002/ijop.12488
|View full text |Cite
|
Sign up to set email alerts
|

The importance of body satisfaction to physical self‐concept and body mass index in Spanish adolescents

Abstract: This research examines the association between measured body mass index (BMI) and the perception of BMI by young students. Moreover, this research tests the importance of BMI and self-concept, in order to predict body dissatisfaction in high school students. The sample consisted of 2087 individuals from different high schools in Extremadura, Spain, both males (n = 1046) and females (n = 1041), ranging in age from 15 to 17 years old (M = 15.42; SD = 0.86). Initially, participants' BMIs were assessed through ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
12
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 23 publications
7
12
2
1
Order By: Relevance
“…Moreover, an important issue to highlight is the importance of BMI and perception of appearance in boys but not in girls. This result is consistent with previous outcomes [2][3][4]25] which found lower scores in appearance in boys compared to girls, as well as a strong relationship between BMI and appearance. This might be explained through the greater participation in physical activities and sports among male sex, which exclude and/o identify those boys who do not engage in, affecting their perception of appearance [5].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Moreover, an important issue to highlight is the importance of BMI and perception of appearance in boys but not in girls. This result is consistent with previous outcomes [2][3][4]25] which found lower scores in appearance in boys compared to girls, as well as a strong relationship between BMI and appearance. This might be explained through the greater participation in physical activities and sports among male sex, which exclude and/o identify those boys who do not engage in, affecting their perception of appearance [5].…”
Section: Discussionsupporting
confidence: 93%
“…Taking into account previous research and according to the relationship between body satisfaction and physical activity, the authors have found negative associations between body satisfaction and physical activity in both sex, emphasizing that low body satisfaction may be a barrier to engaging in physical activity [4,12,26,31]. Thus, the aims of the study were to know the differences between anthropometric variables and fitness in function of the perceived self-concept levels, as well as test the differences between anthropometric variables and fitness regarding body dissatisfaction level in boys and girls.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations